Waist Circumference Cutoff Points to Predict Obesity, Metabolic Syndrome, and Cardiovascular Risk in Turkish Adults - Alper Sonmez; Fahri Bayram; Cem Barcin; Muge Ozsan; Ahmet Kaya; Vedia Gedik (International Journal of Endocrinology)
Objective. The waist circumference (WC) cutoff levels defined for the Caucasian people may not be representative for different ethnic groups. We determined sex specific WC cutoff points to predict obesity, metabolic syndrome, and cardiovascular risk in Turkish adults. Design and Methods. The demographic characteristics of 1898 adult males and 2308 nonpregnant females from 24 provinces of 7 different regions of Turkey (mean age 47 ± 14 yrs) were evaluated. Results. The WC levels of 90 cm and 100 cm define overweight and obese males while the levels of 80 cm and 90 cm define overweight and obese females. With these cutoff values, 239 additional males (12.6%) are diagnosed as overweight and 148 additional males (7.8%) as obese. Instead, 120 females (5.1%) are free of being labeled as obese. Conclusions. This is the first nationwide study to show the action levels of WC for overweight and obese Turkish adults. The ideal cutoff levels of WC to predict metabolic syndrome are 90 cm and 80 cm for Turkish adult men and women, respectively. These values are easy to implement and suggested to be used by the physicians dealing with cardiometabolic disorders in Turkey.